Trivalent cation-induced phase separation in proteins: ion specific contribution in hydration also counts. Issue 38 (23rd September 2022) - Saha, Ria; Mitra, Rajib Kumar
Abstract : Trivalent metal ions induce microscopic liquid–liquid phase separation (LLPS) in negatively charged globular proteins. Explicit change in the hydration associated with ion-induced protein rich LLPS droplet formation is probed here using THz spectroscopy. Abstract : Multivalent (specifically trivalent) metal ions are known to induce microscopic phase separation (commonly termed as liquid–liquid phase separation (LLPS)) in negatively charged globular proteins even at ambient temperatures, the process being mostly driven by protein charge neutralization followed by aggregation. Recent simulation studies have revealed that such self-aggregation of proteins is entropy driven; however, it is associated with a solvation effect, which could as well be different from the usual notion of hydrophobic hydration. In this contribution we have experimentally probed the explicit change in hydration associated with ion-induced LLPS formation of a globular protein bovine serum albumin (BSA) at ambient temperature using FIR-THz FTIR spectroscopy (50–750 cm −1 ; 1.5–22.5 THz). We have used ions of different charges: Na +, K +, Ca 2+, Mg 2+, La 3+, Y 3+, Ho 3+ and Al 3+ . We found that all the trivalent ions induce LLPS; the formation of large aggregates has been evidenced from dynamic light scattering (DLS) measurements, but without perturbing the protein structure as confirmed from circular dichroism (CD) measurements. From the frequency dependent absorption coefficient ( α ( ν )) measurements in the THz frequency domain we estimate the various stretching/vibrational modes of water and we found that ions, forming LLPS, produce definite perturbation in the overall hydration, the extent of which is ion specific, invoking the definite role of hydrophilic (electrostatic) hydration of ions in the observed LLPS process.